Містечко Трипілля та його власники Дідовичі-Трипольські у XVI – першій половині XVII ст.: невідомі сторінки історії - Білоус, Н. (Краєзнавство, 2019)
У статті висвітлюються невідомі сторінки історії Трипілля (суч. село Обухівського р-ну Київської обл.) за литовсько-польської доби, зокрема надання йому магдебурзького права і міського статусу королем Стефаном Баторієм у 1580 р. Віднайдений авторкою пергаментний оригінал привілею
на магдебурзьке право Трипіллю є цікавою і рідкісною знахідкою. Він походить з архіву князів Сангушків, нині зберігається у Державному архіві Польщі в м. Краків (відділення на Вавелі), його текст публікується наприкінці статті і вводиться до наукового обігу. The article is devoted to the research of the unknown pages of the history of Trypillia (a village of
Obukhiv district of Kyiv region) during the Lithuanian-Polish period, in particular, the act of granting of the
Magdeburg law and the urban status for the town by King Stephan Bathory in 1580, based on the sources
from Cracow and Kyiv archives. It was discovered the original chartered right of the Magdeburg city-law
for Trypillia. This is an interesting and rare artifact. The document originates from the Archive of Sangushko
family. The archive of these princes is located in the State Archive of Poland in Cracow (Wawel department);
the text of the manuscript is published at the end of the article. The initiators that granted the Magdeburg
law for Trypillia were its owners: the members of the old local boyar family of Didovych-Trypilsky, the sons
of Vasyl’: Fedir the Elder, Zhdan, Hapon and Fedir Jr. It also tells about some members of this family
and the difficulties with the acquisition and the sale of their estates in Kyiv region and Ovruch district,
inter-neighborhood and family conflicts in the XVIIth – the first half of the XVIIth century. For the purpose
of further elaboration on this topic, previously unknown archives from Krakow and Kyiv have been incorporated.
The research methodology is based on the principles of historicism, systemicity, science, interdisciplinary.
The following general-historical methods have been used: historical-genetic, terminological analysis, comparative,
typological. The authors adhere to the civilizational approach and principles of cultural and intellectual
history. The author came to the conclusion that during the investigated period there were significant changes in
the history of Trypillia: thanks to the active work of its owners, from a small village, it became a town with
the Magdeburg Law, a castle and a parish. In the middle of the XVIIth century, the Didovichy-Trypilsky
family has increased substantially, which led to the dispersal of the lands in its’ ownership among the numerous
heirs who, in search of profits, pursued an active land policy (leasing out separate estates, keeping
the other owners away from the village, seeking to expand their lands though invasion of their neighbors,
etc.), often using illegal means, which made the family increasingly unpopular among its peers. They remained
inactive, however, when it came to the local political scene and were usually not elected into the voivodeship governments, with the exception of Fedir Vasylovych (the Senior), who was elected ambassador to the Sejm in 1572 and became a deputy to the Lublin Tribunal in 1592. All members of the family remained faithful to Orthodoxy. Certain circumstances forced them to sell their estates in the Kyiv region and to settle down in the Ovruch region, where they laid strong roots. During the Cossack Revolution of the middle of the
XVIIth century, the town of Ovruch became a Cossack stronghold. It permanently lost its’ status of the city
with the Magdeburg Law. And in the postwar years, the Trypillia Castle gradually collapsed, turning into ruins.